Inter-set stretch: a preliminary randomized controlled comparison of knee extension strength performance in recreationally trained individuals: Inter-set stretch no decrease in performance in strength - P. Siqueira, Josivam; P. Lopes, Daniel; Inacio, Pedro Augusto; S. Silva, Renato André; F. Fonseca, Douglas; D. Bittar, Roberto; C. A. Rezende, Andréa; A. Caixeta, Davi; F. Moreira, Linda Denise; B. Lopes-Martins, Rodrigo Alvaro; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: The administration of inter-set stretching appears to be an innovative strategy for increasing volume load (VL). However, the literature is still controversial about these effects. Furthermore, no study has evaluated the effects of inter-set stretching on training impulse (TRIMP) outcomes. Objective: To compare the effect of anterior chain stretching between sets on total repetition volume (TV) and VL and TRIMP in the knee extension exercise. Methods: Eleven men were recruited and performed 3 visits to the laboratory. In the first visit, a maximum repetition test was performed on both legs separately (1RM). In the second visit, the leg to be trained was randomly selected. After a 5-minute warm-up, each subject performed 4 sets at 70% of 1RM (passive rest). In the last visit, after warm-up, the subjects performed the same 4 sets at 70% of 1RM, however, differing only in the stretching between sets (2 min between sets). For the stretching protocol, the anterior chain was considered, 20 seconds, at maximum condition. The OMNI-res scale was applied. VL was calculated based on VT x external load and TRIMP based on VL x OMNI-Res. Results: The Kruskal-Wallis test showed no significant differences between the intervention groups (p = 0.884; p = 0.564; p = 0.530; p = 0.947; respectively for all 4 sets. The independent samples t-test showed no differences for the TV (34.3 ± 4.9 vs. 33.9 ± 6.3 repetitions; p = 0.881, respectively for no stretching vs. stretching). The independent t-test also showed no differences between the VL (1405.3 ± 515.8 vs. 1367.0 ± 454.0; p = 0.855, respectively for no stretching vs. stretching). The TRIMP did not show differences between the groups (p = 0.182), as well as the OMNI-RES (p = 0.659; p = 0.100; p = 0.311; p = 0.635, respectively for sets 1, 2, 3 and 4). Conclusion: 20 seconds of inter-set stretching did not influence the TV of the sets, the VL, the OMNI-Res and the TRIMP of the session.